(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In wireless sensor networks that consist of a number of power constrained sensor nodes, the foremost challenges are the limited energy and system lifetime. Therefore, designing efficient routing protocols, which prolong the network lifetime, is one of the most critical issues. This paper evaluated several clustering algorithms, namely: Highest Degree Clustering Algorithm (HDCA), and Lowest Identifier Clustering Algorithm (LIDCA) under three metrics: throughput, Packets Delivered Ratio Factor (PDR) and network lifetime. One of the most important challenges facing Mobile Ad hoc Networks is saving energy that led to a longer network lifetime, which is why we proposed a new clustering algorithm that is considered to be more efficient under network lifetime, and it compared to the clustering algorithms mentioned above. Our experiment occurrences showed that the proposed clustering algorithm supplied a relatively better network lifetime and a more efficient energy distribution for the nodes.